RANCANGAN SISTEM INFORMASI AKADEMIK SEKOLAH BERBASIS LARAVEL - Henky Andema (JURSIMA, 2021)
The school is a tiered and continuous educational unit in order to carry out learning and teaching activities, providing the best service facilities for students. Problems in scheduling often occur, one of which is in the world of education, where this is a fairly complicated problem between teachers and lessons. A good step in using information technology is to create a Laravel-based academic scheduling system. Laravel-based academic scheduling information system design is expected to increase time savings. Where scheduling is actually very necessary in various activities, considering that if the scheduling system is good, it will indirectly have an impact on increasing the efficiency of existing resources